FAKTOR-FAKTOR YANG MEMPENGARUHI PENYIAPAN DAN PENGGUNAAN INFORMASI AKUNTANSI PADA PERUSAHAAN KECIL DAN MENENGAH DI JAWA TENGAH - Solovida, Grace Tianna (PRESTASI, 2010)
In capability in accounting is one of the main factors resulting in difficulty and failure for the small and medium enterprises to expand their business. The researcher conducted a study of factors influencing on accounting information preparation and apllication at the small and medium enterprises. The investigation on influence of managerâs length of time in managing the current enterprise, business size, business age, owner/managerâs educational background, training on accounting that the owner/manager has experienced, the industrial sector, and organitationâs culture on the preparation and apllication used multi regression analysis. The objectiveÂ ofÂ this study was to provide empirical evidence of the preparation and application of accounting information at small and medium enterprises in Central Java.Â Â Â Â The sampling method used was convenience sampling on enterprises on city/district of Semarang, Kudus, Pekalongan, Solo Sukoharjo, Klaten and Tegal. Data collection were conducted through surveyers and interview used questionnaires. Of 430 respondents, 122 were the small enterprises which had up to 19 employees. The other 308 enterprises were medium enterprises which had 20 to 99 employees.Â Â Â Â The results of this study indicate that managerâs length of time in managing the current enterprise, owner/managerâs education background, training on accounting that the owner/manager has experienced, business age, and organizationâs culture have significant influence on the accounting information preparation and application. All the independent variables, except the industrial sector, and business size variable, have significant influence on the accounting information preparation and application at the small and medium enterprises.Keywords : the small and medium enterprises, the accounting information preparation and application, managerâs length of time in managing the current enterprise, business size, business age, owner/managerâs educational background, training on accounting that the owner/manager has experienced, the industrial sector and organizationâs cultureÂ